Application of plowing extrusion-cutting for manufacturing array structural fins. (June 2022) - Zhang, Baoyu; Shen, Pengyu; Zhang, Jiayang; Zeng, Yuning; Pang, Xueqin; Deng, Wenjun
Abstract: Plowing extrusion-cutting (PE-C) is proposed as a new turning method for manufacturing functional structure strips with excellent forming performance, which can be applied as high-efficiency three-dimensional (3D) fins for cooling electronic devices. Experimental investigations were conducted to clarify the characteristic features, performance, and forming mechanism. During PE-C, a plowing tool was applied for shaping metal surfaces before the conventional cutting. Thus, two critical stages of plowing extrusion (PE) and cutting separation were sequentially involved. Results showed that three novel functional structures were obtained, i.e., grooved, dorsal fin-like, and bamboo shoot-like structures. A large feed f and cutting velocity V c had a positive effect on forming the dorsal fin-like structure. The grooved structure was prone to forming with a small f and large tool rake angle γ c, while the bamboo shoot-like structure tended to form at small V c and γ c . Intense tensile stress was generated by excessive metal accumulation during PE stage; once its value surpassed the break limit, the metal underwent ductile fracture and turned into a dorsal fin-like structure. While the bamboo shoot-like structure depended on ductile-to-brittle shear deformation during the cutting separation stage. The excellent forming performance was also reflected in their high fin height (> 3 mm), large aspect ratio (> 5), and low base thickness ratio (< 10%). These results illustrate that PE-C has excellent potential in manufacturing 3D array fins, which are suitable for heat transfer applications.